The triangle of inequality in dental services: arguments for a new conceptual framework - Arash Ghanbarzadegan; Peivand Bastani; Madhan Balasubramanian; David Brennan; Lisa Jamieson (BMC, 2022)
Abstract This short communication paper aimed to compile the main determinants of inequality in dental services by distinguishing between access, utilisation, and provision of dental services. Recent findings integrated, and a dedicated conceptual framework entitled "Triangle of inequality in dental services" has been suggested. These can contribute a rich knowledge in this area and open a new window for policymakers and researchers to seek applied interventions to decrease inequality and improve access and utilisation in communities. This paper aims to synthesise the available evidence and add value to the scope. It highlights a dedicated concept for inequality in dental services beyond other areas of public health.